DPRK’S NUCLEAR CONUNDRUM AND THE U.S.-NORTH KOREA NEGOTIATIONS: A NEVER-ENDING SAGA - M, Mayilvaganan; Khatoon, Nasima (WILAYAH: The International Journal of East Asian Studies, 2023)
The challenge of nuclear proliferation in the Korean peninsula since 2006 with the Democratic People’s Republic of Korea’s (DPRK) first nuclear test had not only drawn the global attention but created a perilous situation on the peninsula. Further the Hwasong-15 Intercontinental Ballistic Missile (ICBM) of DPRK that was tested in February 2023 and thereafter has heightened tensions between Washington and Japan with Pyongyang. The United States’ (U.S.) diplomatic efforts to engage North Korea through bilateral means in recent times resulted in the first historic summit in Singapore (2018) and later in Vietnam (2019). Though these are undoubtedly positive developments, however, in the absence of any tangible deal after the Hanoi summit, the big question remains will the U.S. and North Korea end their mutual misperceptions, and work towards a viable solution. At the moment, the very fact that since 2019, the U.S. and North Korea have had no official dialogues is evident that misperceptions and distrust continues and finding any sort of solution is going to be a very difficult task now that North Korea has closed its borders since the COVID-19 pandemic started. The more isolated Pyongyang is, the more belligerent it will become in testing its missiles.